Answer:
Step-by-step explanation:
You don't specify what you're supposed to do, so I'll make an educated guess.
Given the sequence f(1) = 4, f(n) = f(n − 1) + 11, find the first 5 terms:
f(1) = 4
f(2) = f(2 - 1) + 11 = f(1) + 11 = 4 + 11 = 15
f(3) = f(2) + 11 = 15 + 11 = 26
f(4) = f(3) + 11 = 26 + 11 = 37
f(5) = 37 + 11 = 48
29% would be the answer if you are rounding up
I need help on that to. We have a test tomorrow and I can't figure it out and I need help:(
Step-by-step explanation:
b=a-80
c=b-61
c=a-141
a+b+c=3a-221=430
3a=651
a=217 & b =137 & c=76